2011
DOI: 10.1590/s1677-55382011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamics in women from menopause to oldest age: what motive? what diagnosis?

Abstract: Purpose: To analyze age-associated changes as a motive for urodynamics and urodynamic diagnosis in community-dwelling menopausal women and to discuss the role of menopause and ageing. Materials and Methods: Four hundred and forty nine consecutive menopausal women referred for urodynamic evaluation of lower urinary tract (LUT) symptoms, met the inclusion criteria and were stratified into 3 age groups: 55-64 years (A), 65-74 years (B), and 75-93 years (C). Comprehensive assessment included previous medical histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Several subsequent studies have evaluated the prevalence of detrusor underactivity in women in the ambulatory setting [10,13,14]. Groutz et al [13] interviewed 206 consecutive women with mean age 62.6 in a urogynecology practice for symptoms of ‘voiding difficulties’, specifically: incomplete emptying, double voiding, intermittent voiding, weak stream, hesitancy, straining to void, positional voiding, and need for prolapse reduction.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Several subsequent studies have evaluated the prevalence of detrusor underactivity in women in the ambulatory setting [10,13,14]. Groutz et al [13] interviewed 206 consecutive women with mean age 62.6 in a urogynecology practice for symptoms of ‘voiding difficulties’, specifically: incomplete emptying, double voiding, intermittent voiding, weak stream, hesitancy, straining to void, positional voiding, and need for prolapse reduction.…”
Section: Epidemiologymentioning
confidence: 99%
“…In a study of postmenopausal women age 55 and older, Valentini et al [14] identified detrusor underactivity, defined as ‘impaired detrusor contraction leading to prolonged voiding time and high residual volume,’ in 62/449 (14%) consecutive patients undergoing UDS. The motive for UDS was incontinence in two-thirds of patients.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 449 women, Valentini et al found predominance of impaired detrusor contractility and high PVR in patients 75-93 years old compared to younger age groups [8]. The elderly are more predisposed to fecal impaction, impaired mobility, and use of multiple medications that can affect the detrusor function [9].…”
Section: Obstructive Lutsmentioning
confidence: 99%
“…Factors causing and aggravating urinary incontinence include [1,[14][15][16][17] It is believed that women performing advanced endurance sports are at a risk of developing urinary incon-der were the most common diagnoses in the third age group. The urge incontinence was not linked to age in any way [23]. Different perspective comes from a study by Findink et al, who established that urge incontinence is most prevalent among women after menopause [24].…”
Section: Menopause and Age And Urinary Incontinencementioning
confidence: 99%